2016
DOI: 10.5860/crl.77.5.631
|View full text |Cite
|
Sign up to set email alerts
|

The Value of Academic Libraries: Library Services as a Predictor of Student Retention

Abstract: This study examined the predictive relationship between library use by individual students and their retention status in university settings. The methodology builds on a small number of previous studies to examine library use at the individual level to determine if use of specific library services is predictive of retention for freshmen and sophomores. Binary logistic regression yielded results that indicate a strong positive predictive relationship between library use of any kind with both freshmen and sophom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 17 publications
0
27
0
1
Order By: Relevance
“…A significant number of studies, 46 of the 54 examined, imply transferring individual-level data between the library and a central university office (Allison, 2015;Black & Murphy, 2017;Bowles-Terry, 2012;Çetin & Howard, 2016;Collins & Stone, 2014;Coulter, Clarke, & Scamman, 2007;Cox & Jantti, 2012a, 2012bde Jager et al, 2018;Fransen & Peterson, 2016;Goodall & Pattern, 2011;Haddow, 2013;Haddow & Joseph, 2010;Jantti, 2016;Jantti & Cox, 2013;J. L. Jones, 2010;Kot & Jones, 2015;LeMaistre, 2015;LeMaistre et al, 2018;Massengale, Piotrowski, & Savage, 2016;McCarthy, 2017;Montenegro et al, 2016;Murray et al, 2016;Nackerud et al, 2012Nackerud et al, , 2013Odeh, 2012;Pepper & Jantti, 2015;Renaud et al, 2015;Scarletto et al, 2013;Scott, 2014;Soria et al, 2014Soria et al, , 2017aSoria et al, , 2017bSoria et al, , 2013Soria et al, , 2015Squibb & Mikkelsen, 2016;Stemmer & Mahan, 2015Stone, Pattern, & Ramsden, 2012;Thorpe et al, 2016;…”
Section: Securitymentioning
confidence: 99%
See 3 more Smart Citations
“…A significant number of studies, 46 of the 54 examined, imply transferring individual-level data between the library and a central university office (Allison, 2015;Black & Murphy, 2017;Bowles-Terry, 2012;Çetin & Howard, 2016;Collins & Stone, 2014;Coulter, Clarke, & Scamman, 2007;Cox & Jantti, 2012a, 2012bde Jager et al, 2018;Fransen & Peterson, 2016;Goodall & Pattern, 2011;Haddow, 2013;Haddow & Joseph, 2010;Jantti, 2016;Jantti & Cox, 2013;J. L. Jones, 2010;Kot & Jones, 2015;LeMaistre, 2015;LeMaistre et al, 2018;Massengale, Piotrowski, & Savage, 2016;McCarthy, 2017;Montenegro et al, 2016;Murray et al, 2016;Nackerud et al, 2012Nackerud et al, , 2013Odeh, 2012;Pepper & Jantti, 2015;Renaud et al, 2015;Scarletto et al, 2013;Scott, 2014;Soria et al, 2014Soria et al, , 2017aSoria et al, , 2017bSoria et al, , 2013Soria et al, , 2015Squibb & Mikkelsen, 2016;Stemmer & Mahan, 2015Stone, Pattern, & Ramsden, 2012;Thorpe et al, 2016;…”
Section: Securitymentioning
confidence: 99%
“…Library analytics projects span a range of practices with respect to data minimization. Eight projects encompass a particularly wide range of data collection (Kot & Jones, 2015;Massengale, Piotrowski, & Savage, 2016;Murray et al, 2016;Nackerud et al, 2013;Soria et al, 2014Soria et al, , 2017aSoria et al, , 2013Soria et al, , 2015. One expansive example is Massengale et al (2016), in which library data was collected on "students physically entering the building, students receiving instruction from a librarian, students visiting the Research Help Office (RHO), students checking out laptops, students using interlibrary loan, students reserving study rooms, students placing requests for 3-D printer usage, and students accessing our online resources" (p. 230).…”
Section: Data Collection and Usementioning
confidence: 99%
See 2 more Smart Citations
“…Nine recent studies examined by the authors found that a combination of library space, instruction, and resource usage by FTIC students was positively associated with retention, GPA, or both (Kot & Jones, 2015;Soria et al, 2013Soria et al, , 2014Soria et al, , 2017aSoria et al, , 2017bHaddow, 2013;Murray, Ireland, & Hackathorn, 2016;Stemmer & Mahan, 2016;Stone & Ramsden, 2012). Note that of the studies examined, most focused on library space and resource usage effects on student outcomes which included workstation logins, study room usage, e-resources and print books usage, interactions with library personnel, use of ILL and reference, and other similar resources.…”
mentioning
confidence: 99%